Seasonal variability in voluntary dive duration of the Mediterranean loggerhead turtle, Caretta caretta - Bentivegna, Flegra; Hochscheid, Sandra; Minucci, Carmen (Scientia marina, 2003)
We characterised the effect of seasonal fluctuations in water temperature (Tw) on the nonventilatory period (NVP) of Mediterranean loggerhead turtles, Caretta caretta. Ten captive turtles, that were subject to the natural variations in Tw found in the Gulf of Naples, dived significantly longer when Tw decreased. More than 50% of summer and winter dives lasted between 2 and 10 min; the maximum dive duration (120 min) occurred in winter at a Tw of 13°C. The longest NVP coincided with a low level of activity and a lower food consumption. This, and a reduced metabolic rate consequent to acclimatisation to a low Tw were likely to have influenced NVP.